2015
DOI: 10.14503/thij-14-4424
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exchange for Urgent Apixaban Reversal in a Case of Hemorrhagic Tamponade after Pacemaker Implantation

Abstract: We report the case of an 82-year-old A pixaban is a novel oral anticoagulant (NOAC) that is used to prevent stroke in patients who have nonvalvular atrial fibrillation (AF). This drug has predictable therapeutic levels that do not require laboratory monitoring; however, there is no specific antidote to reverse its toxicity.1,2 We present a case of hemorrhagic pericarditis and cardiac tamponade after pacemaker implantation in a patient who was taking apixaban because of AF. Novel therapy and subsequent treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…A case report by Lam et al demonstrated the effect of TPE on apixaban. Anti‐Xa activity calibrated for LMWH was elevated at 0.84 IU/mL prior to TPE and decreased to 0.35 IU/mL following TPE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A case report by Lam et al demonstrated the effect of TPE on apixaban. Anti‐Xa activity calibrated for LMWH was elevated at 0.84 IU/mL prior to TPE and decreased to 0.35 IU/mL following TPE.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, anti‐Xa levels are consistently shown to decline. This decline may be explained by a concurrent decrease in the anticoagulant being measured, as studies suggest that TPE removes anticoagulants . Therefore, a decrease in the levels of the anticoagulant being measured in the assay likely contributes to the post‐TPE decline in anti‐Xa levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…93 The measured anti-FXa level using a heparin calibrator dropped from 0.76 to 0.22 IU/mL after a two-hour exchange with 3 L of FFP and calcium replacement. The anti-FXa activity measured in the plasma waste was 0.82 IU/mL.…”
Section: S21mentioning
confidence: 97%
“…There is very limited data published on the anticoagulant management in patients undergoing TPE . As illustrated in Table , replacement fluid containing some or all plasma or cryoprecipitate would be used by 34.5%‐67.1% of respondents with the common anticoagulants unfractionated heparin, low molecular weight heparin, and warfarin.…”
Section: Discussionmentioning
confidence: 99%